2021
DOI: 10.1016/j.jenvman.2021.112751
|View full text |Cite
|
Sign up to set email alerts
|

Does green financing help to improve environmental & social responsibility? Designing SDG framework through advanced quantile modelling

Abstract: Striving to achieve the Sustainable Development Goals (SDGs), countries are increasingly embracing a sustainable financing mechanism via green bond financing. Green bonds have attracted the attention of the industrial sector and policymakers, however, the impact of green bond financing on environmental and social sustainability has not been yet been confirmed. There is no empirical evidence on how this financial product can contribute to achieving the goals set out in Agenda 2030. In this study, we empirically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(101 citation statements)
references
References 55 publications
3
98
0
Order By: Relevance
“…The necessity for innovative financing instruments that can mobilize funds toward sustainable development has increased for both developed and developing economies as a result of the COVID-19 pandemic, an unprecedented global catastrophe that has reversed much of the world’s progress in sustainability (United Nations, 2021 ). Though many researchers are addressing this need through studies on socially responsible investing, climate financing, green financing, impact investing, carbon financing, and energy financing, most results remain inconclusive as the field continues to provide limited insights on broad range of financial markets, especially emerging financial markets other than China (Ari & Koc, 2021 ; Sinha et al, 2021 ). Some researchers have reasoned that funding for sustainable finance and sustainable development continues to be developing, and thus, more empirical evidence in both established and emerging markets is needed (Clark et al, 2018 ).…”
Section: Forging the Way Forwardmentioning
confidence: 99%
“…The necessity for innovative financing instruments that can mobilize funds toward sustainable development has increased for both developed and developing economies as a result of the COVID-19 pandemic, an unprecedented global catastrophe that has reversed much of the world’s progress in sustainability (United Nations, 2021 ). Though many researchers are addressing this need through studies on socially responsible investing, climate financing, green financing, impact investing, carbon financing, and energy financing, most results remain inconclusive as the field continues to provide limited insights on broad range of financial markets, especially emerging financial markets other than China (Ari & Koc, 2021 ; Sinha et al, 2021 ). Some researchers have reasoned that funding for sustainable finance and sustainable development continues to be developing, and thus, more empirical evidence in both established and emerging markets is needed (Clark et al, 2018 ).…”
Section: Forging the Way Forwardmentioning
confidence: 99%
“…Many businesses have already begun to adopt sustainability practices for environmental protection and each work description has started to directly provide at least one ecological maintenance requirement and even ecological concern [24]. The green recruiting and selection process is based on environmentally friendly methods for recruitment such as internet resources and reduced paper use during the recruitment phase, and the use of green attitudes at selection [26]. The green skills of individuals are essential to environmental success [27].…”
Section: Green Human Resource Management and Environmental Performancementioning
confidence: 99%
“…The outcomes of Ding et al' (2021) study reported a negative association between technological advancement and carbon emissions in the G-7 countries. However, the results of Sinha et al's (2021) study revealed that technological advancement led to an increase in carbon emissions in the selected Asia Pacific countries.…”
Section: <Insert Table-6>mentioning
confidence: 93%